Group approach to solving the tasks of recognition - Amirgaliyev, Yedilkhan; Berikov, Vladimir; Cherikbayeva, Lyailya S.; Latuta, Konstantin; Bekturgan, Kalybekuuly (Yugoslav Journal of Operations Research, 2019)
In this work, we develop CASVM and CANN algorithms for semi-supervised classification problem. The algorithms are based on a combination of ensemble clustering and kernel methods. Probabilistic model of classification with use of cluster ensemble is proposed. Within the model, error probability of CANN is studied. Assumptions that make probability of error converge to zero are formulated. The proposed algorithms are experimentally tested on a hyperspectral image. It is shown that CASVM and CANN are more noise resistant than standard SVM and kNN.